PERAN PEMERINTAH DAERAH MEWUJUDKAN KOTA SEHAT (Inisiasi Membangun Kota Sehat di Semarang) - Indra Kertati, M.Si (Jurnal Riptek, 2017)
Healthy city is a dream for every citizen. To gain longer life and reaching happiness in life is not naive. To achieve a city with no health dimension is not easy. There are key indicators, main indicators and operational indicators to be met. Hence, to reach a healthier city could not be able to be fed by the government itself. Healthy cities should be done by multi stakeholders, communities, business owners, religious leaders, community leaders, and the government should work together to make this happen. The city of Semarang has proved its recognition by the Ministry of Health of the Republic of Indonesia with a healthy city award with a classification of “Padapa” or a healthy city award in the consolidation of the Ministry of Health.